2021
DOI: 10.1002/brb3.2472
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentration of zinc is elevated in clinically stable bipolar disorder patients

Abstract: Background Bipolar disorder (BD) is a chronic psychiatric disorder characterized by recurrent mood episodes interspersed with euthymic periods. A growing number of studies have indicated that zinc plays an important role in coordinating immune responses, as well as being involved in synaptic transmission. In the current study, we set out to measure serum levels of zinc in a meticulously phenotyped cohort of 121 euthymic BD subjects and 30 matched controls. Methods Serum levels of zinc were measured by photomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Additionally, treatment with magnesium sulfate in patients with aneurysmal subarachnoid hemorrhage did not affect serum S100B levels [52] while in patients with eclampsia [53] and neonatal hypoxicischemic encephalopathy [54], this treatment lead to the decrease in CSF and serum S100B levels, respectively. Regarding the association of YKL-40 with metals, we found only one study in patients with bipolar disorder that showed no association between serum Zn and serum YKL-40 levels [55]. Regarding NFL, studies in experimental animals showed that As treatment leads to NFL disappearance [56], while Al treatment reduced NFL mRNA levels [57].…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, treatment with magnesium sulfate in patients with aneurysmal subarachnoid hemorrhage did not affect serum S100B levels [52] while in patients with eclampsia [53] and neonatal hypoxicischemic encephalopathy [54], this treatment lead to the decrease in CSF and serum S100B levels, respectively. Regarding the association of YKL-40 with metals, we found only one study in patients with bipolar disorder that showed no association between serum Zn and serum YKL-40 levels [55]. Regarding NFL, studies in experimental animals showed that As treatment leads to NFL disappearance [56], while Al treatment reduced NFL mRNA levels [57].…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, zinc levels do not significantly differ between the BDD group and HC, suggesting unique aspects of zinc metabolism or homeostasis in BD [60]. This lack of difference could reflect specific physiological or compensatory responses in BD related to zinc regulation, distinct from those in UD [29].…”
Section: 2mentioning
confidence: 83%